Justice in Malaysian society: Islamic finance and social cohesion / Nur Khalidah Dahlan... [et al.] - Dahlan, Nur Khalidah; Palil, Mohd Rizal; Yaa’kub, Noor Inayah; Abdul Hamid, Mohamad (Universiti Teknologi MARA, Perlis, 2014)
The uniqueness of Malaysia is reflected towards its multi ethnicity society and how the society co-exists and accepting each other differences. History has shown that, harmonisation in Malaysian society is essential and should not be taken for granted. As a result, the government will always prioritize on the economy and social aspect in order to achieve peace and harmony among Malaysian. Therefore, by comparing the pertinent literature on Islamic finance and social cohesion theory, this paper seeks to illustrate the link between economy aspect pertaining to the Islamic finance and the social aspect on how its reflect justice to the whole society.